2001
DOI: 10.1002/yea.705
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and sequence of the MIG1 homologue from the yeast Candida utilis

Abstract: The Mig1p repressor from the food yeast Candida utilis has been isolated using a homologous PCR hybridization probe. This probe was amplified with two sets of degenerate primers designed on the basis of highly conserved motifs in the DNA-binding region (zinc-finger domain) from yeast Mig1p and fungi CreA repressors. The cloned gene was sequenced and found to encode a polypeptide of 345 amino acids which shows significant identity with other yeast and fungus repressors in the DNA-binding domain and also with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Finally, the entire sequence of SoMig1p was compared with those from complete Mig1p and CreA sequences of different organisms (Table 1). C. utilis Mig1p (Delfin et al ., 2001) is the most similar to SoMig1p, with 24% identity. This similarity is consistent with the short phylogenetic distance existing between these two organisms (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the entire sequence of SoMig1p was compared with those from complete Mig1p and CreA sequences of different organisms (Table 1). C. utilis Mig1p (Delfin et al ., 2001) is the most similar to SoMig1p, with 24% identity. This similarity is consistent with the short phylogenetic distance existing between these two organisms (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, transcriptional regulators of maltase genes from other yeasts can function in S. cerevisiae . For example, the Mig1 repressor homologues from Candida utilis [27], K. lactis [28] and Schwanniomyces occidentalis [29] complement the Mig1 deficiency in S. cerevisiae , and the MAL activator of C. albicans (CASUC1) can substitute the function of MAL63 activator protein in S. cerevisiae [30]. We inspected the GenBank data resulting from the partial genomic sequencing project of H. polymorpha [31] in order to find nucleotide sequences that might encode homologues of S. cerevisiae MAL activator and Mig1 repressor proteins.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, transcriptional regulators of maltase genes from other yeasts can function in S. cerevisiae. For example, the Mig1 repressor homologues from Candida utilis [27], K. lactis [28] and Schwanniomyces occidentalis [29] complement the Mig1 de¢ciency in S. cerevisiae, and the MAL Fig. 4.…”
Section: Regulation Of the S Cerevisiae Maltase Gene Mal62 In Hp201hmentioning
confidence: 99%
“…Repression of MLS1 occurs through a Mig1 site ( Caspary et al 1997 ). It has been shown that a MIG1 gene deletion in Saccharomyces cerevisiae can be rescued by MIG1 from Candida utilis ( Delfin et al 2001 ) and K. lactis ( Cassart et al 1995 ), indicating that MIG1 has conserved its general function as well.…”
Section: Introductionmentioning
confidence: 99%